FEATURES OF MAGNETIC RESONANCE IMAGRAPHY OF COMMON TUMORS OF THE POSTERIOR CRANIAL FOSSE IN CHILDREN. (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The incidence of brain cancer worldwide is 2.2 per 100,000 in men and 1.4 per 100,000 in women. At the same time, the percentage of brain cancer in male and female children was 18.1% and 17.2%, respectively [1]. Reports from the US Central Brain Tumor Registry indicate that the incidence of brain tumors is 5.47 per 100,000 children under 14 years of age.